Djibouti : Fifth Review Under the Extended Credit Facility Arrangement, Request for Augmentation of Access and Rephasing, Request for Waivers of Nonobservance of Performance Criteria, and Request for Waiver of Nonobservance of Performance Criterion Resulting in Noncomplying Disbursement: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Djibouti. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents findings of the Fifth Review of Djibouti's economic performance under the extended credit facility (ECF) arrangement. The drought in Djibouti has worsened water scarcity, reduced agricultural production and cattle stock, and accelerated refugee inflows. The authorities have requested an augmentation of access under the ECF of 60 percent of quota. As a result of exogenous shocks, financing needs for 2011-12 are expected to be higher than previously projected, despite the pledges from the international community to help Djibouti address the impact of the drought.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet